ธรรมชาติของมนุษย์ ในทัศนะของพุทธทาสภิกขุ - (ดาวใหม่), พระแมน ฐิตเมโธ; มนตราภิบูลย์, มนต์เทียน (วารสาร ศึกษาศาสตร์ มมร, 2018)
บทคัดย่อ               งานวิจัยเรื่อง ธรรมชาติของมนุษย์ในทัศนะของพุทธทาสภิกขุนี้ มีวัตถุประสงค์ ๓ ข้อ คือ  ๑) เพื่อศึกษาธรรมชาติของมนุษย์ในพุทธปรัชญาเถรวาท ๒) เพื่อศึกษาธรรมชาติของมนุษย์ในทัศนะของพุทธทาสภิกขุ ๓) เพื่อวิเคราะห์ธรรมชาติของมนุษย์ในพุทธปรัชญาเถรวาทกับทัศนะของพุทธทาสภิกขุ เป็นการวิจัยเอกสาร  ผลของการวิจัยพบว่า    ๑) ธรรมชาติของมนุษย์ในพุทธปรัชญาเถรวาทตั้งอยู่บนพื้นฐานของทฤษฎีอนัตตา มนุษย์เป็นสัตว์ที่เกิดจากองค์ประกอบด้วยกาย และจิต จิตหรือวิญญาณของมนุษย์มีอยู่จริง โดยอาศัยร่างกายเป็นที่อยู่ เป็นธรรมชาติที่ไม่มีรูปร่าง เป็นนามธรรม มีความสัมพันธ์กับร่างกายและมีความสำคัญกว่าร่างกาย ธรรมชาติของร่างกายมนุษย์มีการเปลี่ยนแปลง ไม่สามารถดำรงอยู่ในภาวะเดิมตลอดไปได้เรียกว่า อนิจจตา และถูกบีบคั้นให้เกิดการเปลี่ยนแปลงภายในอยู่ตลอดเวลาเรียกว่า ทุกขตา จุดหมายสูงสุดที่แท้จริงของชีวิต คือ นิพพาน นิพพานํ ปรมํ สุขํ นิพพาน เป็นบรมสุข           ๒) ธรรมชาติของมนุษย์ในทัศนะของพุทธทาสภิกขุ ได้ใจความว่า มนุษย์มีสัญชาตญาณสัตว์แฝงฝังอยู่จริงหรือ สัญชาตญาณสัตว์คือความหมกมุ่นอยู่ในโลกิยะ มนุษย์หมกมุ่นอยู่กับโลกิยะ และมีความเป็นตัวกู ของกู สัญชาตญาณสัตว์ที่กล่าวนี่เองเป็นสาเหตุแห่งความทุกข์    ๓) วิเคราะห์ทั้งสองทัศนะพบว่า มนุษย์ผู้ประเสริฐหรือมนุษย์ที่มีคุณค่าก็คือมนุษย์ที่สามารถเอาชนะหรือว่าควบคุมสัญชาตญาณสัตว์เหล่านี้ได้นั่นเอง การดำเนินชีวิตที่พระพุทธองค์ทรงแสดงให้มนุษย์เห็นภาวะความจริงของชีวิต นำไปสู่ความดับทุกข์ คือการศึกษาให้เข้าใจถ่องแท้ในอริยสัจ ๔ ชี้ให้เห็นสารัตถะแห่งชีวิตว่า นี่คือความทุกข์ สาเหตุของความทุกข์ ความดับทุกข์ และทางดำเนินให้ถึงความดับทุกข์ คำสำคัญ : พุทธทาสภิกขุ, มนุษย์ จิตใจสูง, คุณธรรม       ABSTRACT      The purposes of this thesis are to describe Human the nature the vision of Buddhadasa Bhikkhu, (1) study human the nature the in Theravada Buddhist Philosophy, (2) study human the nature the vision of Buddhadasa Bhikku, (3) analysis human the nature the vision of Buddhadasa Bhikku, with the concept of human the nature in Theravada Buddhist Philosophy, to consider the socialization process of his thoughts, are applicable to the contemporary social and moral situations. The findings of the study can be summarized as follows.                               (1) Buddhadasa’s thoughts was to larger extent based on Theravada Buddhism which acquired thought his career socialization. The concept of human nature in Theravada Buddhism Philosophy is based on the theory of Anattā (non- self). Human beings are born from two compositions Body, กาย, Mind, Soul, จิต, Human being’s minds or consciousness really exist in human being’s bodies. They are formless’ having connection with bodies and are of importance to bodies. The body of Human beings is an impermanent, changeable (Aniccatā) and is subject to oppression all time, especially, it is subject to suffering (Dukkhatā). The highest of life is “Nibbana”.              (2) Human the nature the vision of Buddhadasa Bhikkhu,  the instinct of every human being has, but the fear of survival of their own selfish needs to Four Noble Truths contain the essence of Buddha's teachings.    (3) The findings indicated the similarity between Buddhism, and Buddhadasa Bhikkhu,   Humans have always and endless needs. The human nature of Buddhism is referred to as "dynamic organism". The body is constantly changing. To strive for the things to meet the needs or difficulties are endless. Lust or craving Make people struggling. Try to do everything to get the desire. Keywords : Buddhadasa, High minded man, moral